Confirming congenital hypothyroidism identified from neonatal screening. - Foo, A. (Ulster Medical Society, 2002)
All patients identified in the neonatal screening programme for congenital hypothyroidism in Northern Ireland between 1983 and 1993 were reviewed. 131 infants were recalled because of TSH elevation of whom 85 proved to have true permanent congenital hypothyroidism, while 44 had transient TSH elevation and 2 cases died before the diagnosis could be confirmed. TSH elevation at presentation was milder in the transient group and these infants were more likely to be unwell and/or suffering from congenital malformation.